2015
DOI: 10.1097/mph.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-associated Neurological Morbidity in the Treatment of Hepatoblastoma

Abstract: Chemotherapy is an essential component of therapy for infants and children with hepatoblastoma. Vincristine has been a mainstay of chemotherapeutic regimens used by North American cooperative groups, based on indirect evidence of benefit and an assumption of minimal added toxicity. European cooperative group trials have reported comparable survival rates using regimens that omit vincristine. Further examination of the risk and benefit profile of vincristine relevant to hepatoblastoma clinical care paradigms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In this study, we found no statistically significant difference in the effectiveness of paclitaxel or vincristine at 0 or 3 months following RLN transection/repair. Vincristine administration in the setting of chemotherapy has been associated with toxicity including neutropenia, neuropathy, and a small therapeutic window . Although low‐dose administration of vincristine following vocal fold paralysis may avoid toxicity and achieve the desired effects, paclitaxel provides an alternative with a possibly wider therapeutic index .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found no statistically significant difference in the effectiveness of paclitaxel or vincristine at 0 or 3 months following RLN transection/repair. Vincristine administration in the setting of chemotherapy has been associated with toxicity including neutropenia, neuropathy, and a small therapeutic window . Although low‐dose administration of vincristine following vocal fold paralysis may avoid toxicity and achieve the desired effects, paclitaxel provides an alternative with a possibly wider therapeutic index .…”
Section: Discussionmentioning
confidence: 99%
“…Vincristine administration in the setting of chemotherapy has been associated with toxicity including neutropenia, neuropathy, and a small therapeutic window. [19][20][21] Although low-dose administration of vincristine following vocal fold paralysis may avoid toxicity and achieve the desired effects, 10 paclitaxel provides an alternative with a possibly wider therapeutic index. 22 Additionally, prior studies have demonstrated that paclitaxel and vincristine have no effect after reinnervation has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is a significant complication of pediatric and young adult cancer therapy and has substantial adverse effects on health‐related quality of life . In addition, neuropathic pain is a dose‐limiting side effect of chemotherapy that can impact the success of treatment and the overall survival . The economic burden of neuropathic pain is considerable, including increased medical costs and loss of productivity for patients and caregivers …”
Section: Introductionmentioning
confidence: 99%
“…Existing data reporting the prevalence of neuropathic pain in pediatric and young adult cancer patients are limited to retrospective chart reviews. These studies have focused on pediatric patients with acute lymphoblastic leukemia (ALL) and hepatoblastoma and found that 29–35% of the patients experienced neuropathic pain associated with receipt of vincristine . These studies are significantly limited by their retrospective nature and are only able to report on what was documented in the medical record.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation